The Conceptualisation of Oloso in Alimoso, Lagos, Nigeria - Adeyinka W. Olarinmoye (MultiTech Publisher, 2025)
This study focuses on the activities of Oloso, that is, prostitutes or commercial sex workers in Alimoso area of Lagos State, Nigeria. The research aims to investigate the classification of oloso, and their mode of operation. It also discussed the sociological factors that influenced ladies and women into oloso and the patterns and trends of behavioural changes among them as well as health implications associated with such trade. Indeed, oloso is among the major social problems in Nigeria and other countries of the world due to its moral and health implications. In all Twenty Five (25) informants were selected through purposive sampling technique. The informants include individuals that were willing to answer the research questions from personal experiences. The findings of the research revealed the various classes of oloso, their mode of operation, sociocultural factors, common behaviourial traits and health implications that are common to them. Peer pressure, poverty, parental negligence and high libido are among the notable factors that influenced ladies and young women to indulge in such practices. From the foregoing, it is recommended that the government, corporate and religious organisations among others should embark on aggressive programmes such as comprehensive sex education, economic empowerment programs, parental and community engagement, mental health support services, health services and safe practices education, social media monitoring and regulation, support networks and rehabilitation and strengthening legal framework and law enforcement. Also, the government should enact and enforce laws that regulate the conduct of olosos. This will help to sanitise and regulate the trade, especially the high rate of girl-child/under age prostitution in the country